Prenatal Cadmium Exposure Is Negatively Associated With Adiposity in Girls Not Boys During Adolescence - Moynihan, Meghan; Telléz-Rojo, Martha Maria; Colacino, Justin; Jones, Andrew; Song, Peter X. K.; Cantoral, Alejandra; Mercado-García, Adriana; Peterson, Karen E. (Frontiers in Public Health, 2019)
Introduction Cadmium is a highly pervasive toxic metal that remains a large public health concern, especially for children where early exposure is associated with depressed growth in infancy and childhood. No study has examined its influence into adolescence, but the peripubertal period may be particularly sensitive to effects of cadmium given the changes in distribution of lean and adipose tissue that vary by sex. Our study examines whether prenatal and concurrent cadmium exposure is associated with adiposity measures at ages 8-15 years in a well-characterized birth cohort. Methods Our sample included 185 adolescents between 8-15 years of age from ELEMENT birth cohorts in Mexico City with complete data on cadmium exposures, anthropometric outcomes, and other covariates (e.g. child age and sex, household socioeconomic status, and maternal smoking history and BMI). Maternal (third trimester) and adolescent urines were analyzed for cadmium using an Inductively Coupled Plasma Mass Spectrometer. Trained personnel obtained anthropometry for adolescents at visit: waist circumference, height and weight, and subscapular, suprailiac, and triceps skinfold thickness. BMI z-scores for age and sex were calculated using the World Health Organization’s reference population. Linear regression models were used to determine the association of prenatal and concurrent urinary cadmium levels with anthropometry, adjusting for covariates and confounders. Results Among 87 males and 98 females, median age was 10 years (IQR 9-11 years). Pregnant women and children had median urinary cadmium concentrations of 0.19 μg/L (IQR 0.12-0.27 μg/L) and 0.14 μg/L (IQR 0.11-0.18 μg/L), respectively. Regression models showed inverse relationships between prenatal cadmium exposure and child adiposity measures: an IQR increase in prenatal cadmium was associated with a percent decrease in BMI z-score (-27%, p=0.01), waist circumference (-3%, p=0.01), and subscapular (-11%, p=0.01), suprailiac (-11%, p=0.02), and triceps (-8%, p<0.01) skinfold thickness. When stratified by sex, these relationships remained significant in females but not males. Conclusions Prenatal cadmium exposure was negatively associated with measures of both abdominal and peripheral adiposity in girls, but not in boys. These results emphasize the sex-dependent adiposity effects of cadmium exposure in utero that persist into adolescence.